2009
DOI: 10.1016/j.cell.2008.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted in Schizophrenia 1 Regulates Neuronal Progenitor Proliferation via Modulation of GSK3β/β-Catenin Signaling

Abstract: SUMMARY The Disrupted In Schizophrenia 1 (DISC1) gene is disrupted by a balanced chromosomal translocation (1; 11) (q42; q14.3) in a Scottish family with a high incidence of major depression, schizophrenia and bipolar disorder. Subsequent studies provided indications that DISC1 plays a role in brain development. Here we demonstrate that suppression of DISC1 expression reduces neural progenitor proliferation, leading to premature cell cycle exit and differentiation. Several lines of evidence suggest that DISC1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
819
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 727 publications
(855 citation statements)
references
References 46 publications
33
819
1
2
Order By: Relevance
“…GSK-3β is an important molecular target downstream of AKT1 and is involved in a series on mechanisms of gene expression, including inactivation of β-catenin (26,42). Previous studies have indicated that AKT1 signaling inhibits GSK-3β activity via phosphorylation (43).…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3β is an important molecular target downstream of AKT1 and is involved in a series on mechanisms of gene expression, including inactivation of β-catenin (26,42). Previous studies have indicated that AKT1 signaling inhibits GSK-3β activity via phosphorylation (43).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that MICOS-OPA1 synergy regulates the response to hypoxia by modulating cristae outlets and decreasing the number of ATP synthases dimers (50). Moreover, hDISC1 has been reported previously to inhibit glycogen synthase kinase 3b (GSK3b) (51), which in turn phosphorylates Drp1, increasing its GTPase activity and mitochondrial recruitment, with the resulting trigger of mitochondrial fragmentation (52). Whether DISC1 modulates mitochondrial dynamics through its function at MICOS or through its control on GSK3b-Drp1 will have to be explored in further investigations.…”
Section: (G-h)mentioning
confidence: 99%
“…Such an interpretation is consistent with the fact that mutations in DISC1, which reduce its inhibitory effect on GSK-3β and is one of the prominent genes mutated in both schizophrenia and BD, results in a decrease in neurogenesis. 26 Single nucleotide polymorphisms (SNPs) of the Bcl-2 gene, which increase the risk of developing BD, are associated with elevated basal Ca 2+ levels and enhanced Ins(1,4,5)P 3 -mediated cytosolic Ca 2+ release. 27 Both Li + and valproate can markedly enhance the level of Bcl-2.…”
Section: Bipolar Disordermentioning
confidence: 99%